Financial Inclusion through Mobile Money in developing countries: the case of Vietnam - Luan-Thanh Nguyen (Digital transformation, cooperation and global integration in the new normal, 2023)
The use of mobile technology services in Vietnam has surged, offering convenience and enhancing various aspects of users' lives. This shift towards wireless connectivity has also affected financial transactions and remittances, aligning with goals of a cashless society and financial inclusion. Mobile money, a widely used mobile service, is examined in this study. We focus on the determinants affecting the adoption of mobile money services, which are of interest to mobile money firms, telecom companies, banks, and developers. Factors like price, social influence, and perceived risk are explored as they influence consumer acceptance. To succeed, service providers must lower costs, emphasize benefits, and ensure seamless functionality. User-friendliness, trust, and data security are essential for sustained adoption and financial inclusion. This study provides insights into mobile money adoption in Vietnam, guiding stakeholders in the mobile technology sector to adapt and thrive in this evolving landscape.
Conference: The second International Conference on Science, Economics and Society Studies, Ho Chi Minh City, 25th August 2023
Keywords: 330; Mobile money; PLS-SEM; Vietnam; UTAUT